Innovación docente con jóvenes interactivos: proyectos sociales reales y estrategias digitales para enseñar comunicación - Bueno Doral, Tamara; Hänninen, Liisa Irene (Estudios sobre el Mensaje Periodístico, 2012)
The present paper shows the results of a new educational innovation methodology, obtained after eight years of application and study at the Faculty of Communication Science, Complutense University of Madrid, and adapted to the requirements of interactive youth. The method is based on real social and professional projects and contemplates interactivity from a double point of view. On one hand, the university in the Web is seen as online interaction, the capacity of lecturers and students to obtain the maximum benefits from the multiple opportunities offered by digital communication to the educational process, and on the other, the university network as the ability of social interaction between the collective of professors, students and the companies and organizations forming the labor market.